Relative improvements between roads and railways and transport carbon dioxide emissions: An environmental Kuznets curve hypothesis test in China - Wang Peng; Yu Xiaoyuan; Nuzul Azam Haron (Sustainable Futures)
The rapid expansion of transport infrastructure during economic development has led to significant increases in carbon emissions, particularly in developing countries. However, the relationship between different transport modes and carbon emissions across development stages remains unclear. This study examines the relationship between the relative improvement of railways to roads (RPR), economic growth, and transport carbon emissions, aiming to verify the Environmental Kuznets Curve (EKC) hypothesis in China's transport sector. Using an ARDL model and bounds testing approach, we analyze Chinese data from 1978 to 2021. The bounds test confirms a long-term cointegration relationship among RPR, GDP per capita, and transport carbon emissions. Both long-term and short-term analyses support the EKC hypothesis, indicating an inverted U-shaped relationship between economic growth and per capita transport carbon emissions. The impact of RPR on per capita transport carbon emissions is significantly positive in both the long and short term. The error correction term shows that approximately 41 % of short-term disequilibrium is corrected within a year, further confirming the long-term relationship between variables. Diagnostic tests and stability analysis ensure the reliability of the model results. The study reveals that the impacts of transport demand, infrastructure investment, and technological progress on carbon emissions vary across different stages of economic development. These findings suggest that developing economies should adopt a dynamic approach to transport infrastructure planning, with early preparation for railway development to avoid carbon emission lock-in effects. For sustainable development, policymakers should align infrastructure investment priorities with economic development stages while promoting cross-regional coordination in transport planning.